Some Effects of(θ,ϕ) −Derivations on Centrally Prime Rings - Jabbar, Adil Kadir; Majeed, Abdulrahman Hamed (Sulaimani Journal for Pure and Applied Sciences, 2008)
In this paper we study some effects of θ φ),( − derivations on centrally prime rings, and we try to extend some results on prime rings which are concerned with θ φ),( − derivations to centrally prime rings and also we determine those conditions under which these extensions are allowed.
Keywords: Derivations; prime rings; centrally prime rings; Lie ideals